Public Perceptions And Acceptance Of Ecoenzyme-Based Environmentally Friendly Soap In Lhokseumawe City - Jannatul Liani; Abdul Malik; Syifa Saputra (RADJA PUBLIKA, 2026)
Ecoenzyme-based soap, formulated using fermented organic waste, may support household-level waste management and greener cleaning practices. This study examined public perceptions, acceptance, and perceived social and environmental implications of ecoenzyme-based environmentally friendly soap in Lhokseumawe City. A convergent mixed-methods design based on the Theory of Planned Behavior was used. Quantitative data were obtained from 54 questionnaire respondents and analyzed descriptively, while qualitative data were collected through in-depth interviews with 10 key informants and analyzed thematically using NVivo 12. Community perception was positive (mean = 4.29), with environmental friendliness receiving the highest rating (mean = 4.72). Acceptance was strong (mean = 4.50), led by interest in using ecoenzyme soap as an alternative to conventional soap (mean = 5.00). Family support, perceived ease of use, environmental benefits, and perceived safety were important enabling factors. However, limited technical knowledge, product availability, and affordability may constrain sustained use. The findings indicate that high stated acceptance reflects behavioral intention rather than verified routine adoption. Education on production and use, quality standardization, and improved access are needed to translate favorable perceptions into sustained household practice